2011
DOI: 10.1007/s11746-011-1813-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on Free Lipase‐Catalyzed Ethanolysis for Biodiesel Preparation in an Oil/Water Biphasic System

Abstract: Using free lipase as the catalyst for biodiesel production has drawn increasing attention in recent years due to its advantages of lower cost and faster reaction rate compared to immobilized lipase. Our previous study showed that free lipase NS81006 could effectively catalyze the methanolysis of renewable oil. Ethanol, derived from renewable biomass, has a greater potential for biodiesel production. In this paper, ethanol was explored for the first time as the acyl acceptor for free lipase-mediated biodiesel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Sample preparation and detection conditions were as described by Ren et al . [ 54 ]. TLC was performed as in our previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation and detection conditions were as described by Ren et al . [ 54 ]. TLC was performed as in our previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the various lipases, free lipase has become a promising biocatalyst for biodiesel production due to the following merits: the cost of free lipase is tens of times lower compared to immobilized lipase based on the same enzymatic activity; and the risk of using free lipase is greatly reduced; free lipase can catalyze biodiesel production in water-containing system, this is very important for non-edible oils feedstock's conversion and the reuse of free lipase can be achieved through membrane recovery [7][8][9][10][11][12]. In our previous study, it was found that a biodiesel yield of over 90% could be obtained with free lipase NS81006-mediated biodiesel production [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the pathway of direct methanolysis exists in the process still need further exploration. In the current paper, an effective free lipase (NS810006) [7,24] was used as catalyst and two full kinetic models considering both two pathways for biodiesel production were proposed. According to the simulation results, the kinetic mechanism of free lipase NS81006 was finally revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial free lipase NS81006 from the genetically modified Aspergillus niger was studied for biodiesel production [160,163]. Fatty acid methyl (FAMEs) and ethyl (FAEEs) esters were produced from soybean oil obtaining yields of 95.1% [160] and 90% [163] respectively. Lipase NS81006 was stable for five batches in the production of FAEEs after simple separation of the water phase [163].…”
Section: Free Lipasesmentioning
confidence: 99%
“…Fatty acid methyl (FAMEs) and ethyl (FAEEs) esters were produced from soybean oil obtaining yields of 95.1% [160] and 90% [163] respectively. Lipase NS81006 was stable for five batches in the production of FAEEs after simple separation of the water phase [163].…”
Section: Free Lipasesmentioning
confidence: 99%